2003
DOI: 10.1159/000070449
|View full text |Cite
|
Sign up to set email alerts
|

Protective Influence of Experimentally Formed Salivary Pellicle on Enamel Erosion

Abstract: The purpose of this study was to evaluate dental erosion in 0.1 and 1.0% citric acid in vitro by several different methods and to assess the protective potential of experimentally formed salivary pellicle (24 h in vitro). Bovine enamel slabs were embedded in epoxy resin and polished. Erosion was performed in citric acid for 1, 5 or 10 min and recorded as microhardness loss, as changes of surface roughness (Ra, Rt and RzDIN) and as calcium release. Additionally, erosive alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1
19

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 24 publications
6
45
1
19
Order By: Relevance
“…17 Analysis of calcium ion release from enamel tissues after demineralization cycles was used as a well-accepted method for the assessment of erosion progression. 25,30 In contrast to the reflection analysis, no statistically significant differences were found in calcium dissolution among all groups at all applied erosion times [ Fig. 7(b)] except enamel samples remineralized in human saliva (group 2) and mineral solution (group 4) after a total of 8 min of erosion (Table 3).…”
Section: Methodsmentioning
confidence: 85%
“…17 Analysis of calcium ion release from enamel tissues after demineralization cycles was used as a well-accepted method for the assessment of erosion progression. 25,30 In contrast to the reflection analysis, no statistically significant differences were found in calcium dissolution among all groups at all applied erosion times [ Fig. 7(b)] except enamel samples remineralized in human saliva (group 2) and mineral solution (group 4) after a total of 8 min of erosion (Table 3).…”
Section: Methodsmentioning
confidence: 85%
“…Therefore, determination of dental enamel dissolution by assessing the amount of calcium or phosphate dissolved from the apatite crystals of dental hard tissue could also be regarded as a possible tool for assessing dental erosions. Hence, some authors had applied calcium determina-tion in erosive, acidic solutions after prolonged contact (range 2 min to 24 h) of the solutions with dental hard tissue using calcium sensitive electrodes, atomic adsorption spectrophotometer or the highly sensitive method of inductively coupled plasma mass spectrometry [68][69][70][71][72] Calcium-sensitive electrodes often need a specific pH of the environment to work precisely. Additionally, cal-cium complexes formed with certain acids (e.g.…”
Section: Chemical Analysis Of Minerals Dissolved In the Erosive Agentmentioning
confidence: 99%
“…LMR is less sensitive to minute changes in mineral content than TMR, because of the use of thicker specimens as compared with TMR. Using LMR, erosion progression in both enamel and dentin has also been assessed [91][92][93] [69][70][71]. In these studies, the method has shown to be suitable to allow for distinction of different preventive treatment modalities resulting in different mineral loss.…”
Section: Chemical Analysis Of Minerals Dissolved In the Erosive Agentmentioning
confidence: 99%
“…This demineralization occurs in a centripetal manner 6 , beginning with the interprismatic area and following through the central region of the prism. The increase of the demineralized area generates a higher surface roughness 7 and decreases the microhardness of dental tissue 8 . In consequence of the alterations caused on surface characteristics, the enamel surface becomes more susceptible to the action of mechanical forces 9 .…”
mentioning
confidence: 99%